Self-satisfaction described by Zuckerman’s alternative five factors of personality - Đorđe Čekrlija; Julie Aitken Schermer (Current Issues in Personality Psychology, 2023)
Background This study investigates the relationships between an individual’s self-satisfaction within different life areas, which correspond to Bracken’s self-concept primary domains (competence, family, social, physical, emotional, and academic domains), and Zuckerman’s Alternative Five-Factor Model of Personality (AFFM). It is supposed that the AFFM, as a psychobiological personality model which allows causal explanations, could provide a comprehensive insight into the nature of satisfaction with self.